Pengaruh Struktur Aset dan Profitabilitas terhadap Struktur Modal pada Perusahaan Perbankan yang terdaftar di Bursa Efek Indonesia Tahun 2014-2020 - Sri Taufil Laily; Lalu Hamdani Husnan; Siti Aisyah Hidayati (Universitas Bumigora, 2022)
The purpose of this study was to determine the effect of asset structure and profitability on the capital structure of banking companies listed on the Indonesian stock exchange in 2014-2020. The type of research used is causal associative with a quantitative approach. The population in this study were all banking companies listed on the Indonesia Stock Exchange in 2014-2020, namely 41 companies. The sample used in this study were 18 companies. The data used are secondary data obtained from www.idx.co.id as well as several company websites that were sampled in the study. The analytical tools used are descriptive statistical tests, classical assumption tests, multiple linear regression, and hypothesis tests consisting of t test, f test, and coefficient of determination R2 with SPSS version 22. The results of this study indicate that asset structure has a negative and significant effect on capital structure, profitability and significant negative effect on capital structure.